Magnitude or Multitude – What Counts? - Lachmair, Martin; Ruiz Fernández, Susana; Moeller, Korbinian; Nuerk, Hans-Christoph; Kaup, Barbara (Frontiers in Psychology, 2018)
Recent studies revealed an association of low or high numbers (e.g., 1 vs. 9) and word semantics referring to entities typically found in upper or lower space (e.g. roof vs. root) indicating overlapping spatial representations. Another line of research revealed a similar association of grammatical number as a syntactic aspect of language and physical space: singular words were associated with left and plural words with right - resembling spatial-numerical associations of low numbers with left and high numbers with right. The present study aimed at integrating these lines of research by evaluating both types of spatial relations in one experiment. In a lexical decision task, pairs of a numerical cue and a subsequent plural noun were presented. For word with spatial associations (e.g., roofs vs. roots) number magnitude was expected to serve as a spatial cue. For spatially neutral words (e.g., tables) numbers were expected to cue multitude. Results showed the expected congruency-effect between the numbers and words with spatial associations (i.e. small numbers facilitate responses to down-words and high numbers to up-words). However, no effect was found for numbers and spatially neutral words. This seems to indicate that spatial aspects of word meaning may be related more closely to the magnitude of numbers than grammatical number is to the multitude reflected by numbers – at least in the current experimental setting, where only plural words were presented.